Perfil epidemiológico do suicídio no município de Altamira - SILVA, Felipe Anaissi Oliveira da (2022)
Introduction: Suicide is characterized as a deliberated act by the individual himself, with the intention of carrying out self-extermination. It is one of the oldest themes related to health, reported in religious texts and in mythologies of ancient peoples. It represents a complex content, studied by several areas of knowledge. It has great relevance because it is a public health problem worldwide, which has high rates in Brazil; and growing trend in the northern region, with emphasis on Altamira. Objectives: The objective of the study is to characterize, through the analysis of secondary data, suicide cases in the city of Altamira-Pará, in the period from 2015 to 2020, as well as to identify risk factors and main methods used in suicide; to investigate possible associations between the casuistry of suicides and the epidemiological profile of the target population. Methodology: This is an observational, descriptive research, with a qualitative and quantitative approach. The group submitted to the study will consist of suicide victims living in the municipality of Altamira or adjacent municipalities who were notified through the Mortality Information System and / or the municipal Legal Medical Institute. As data collection instruments, information from the Mortality Information System (SIM), from the State Health Secretary of Pará (SESPA) and from the Legal Medical Institute (IML) of the municipality of Altamira will be used. The data obtained will be stored in a database, using the Excel platform. The frequencies of the variables will be calculated as simple mathematical ratios and expressed as percentage numbers. Analyzes will be performed based on the chi-square tests; Fisher's exact test; logistic regression test; two-tailed Mann-Whitney test; one-tailed ANOVA test and the Kruskal-Wallis test. The data will be analyzed and the calculations will be made with the aid of the BioEstat 5.0 program. Results: The data provided by the IML between the years 2015 to 2020 were registered 79 cases of suicide in the city of Altamira, of these 22 cases were female and 57 male. Regarding SESPA data for the same period, 49 cases were registered, 19 females and 30 males. SIM data for the years 2015 to 2020 accounted for 47 cases, 18 females and 30 males. The minimum age of suicide cases was 10 years, the maximum 78 years and the average 32 years. Approximately 94% of the suicide cases were by hanging, 70% of the cases were concentrated among singles, around 60% were of the brown race, 42% studied from 8 to 11 years and 32% from 4 to 7 years of study. The analysis of association of categorical variables age (p= 06441), race (p = 0.4858), marital status (p= 0.844), education (p=0.2237) and gender (p=0.8746) with the suicide mode did not show statistically significant results. The analysis of suicide data according to IML showed that the tendency for an increase in the frequency of suicide in the municipality of Altamira is statistically significant, with p-value = 0.004 and R² = 0.8619. Conclusion: It was observed that death by suicide continues to grow in the country and Altamira follows this trend. There is a lack of government programs that work effectively in suicide prevention.